Overexpression of SDF-1[alpha] Enhanced Migration and Engraftment of Cardiac Stem Cells and Reduced Infarcted Size via CXCR4/PI3K Pathway - Wang, Kui; Zhao, Xiaohui; Kuang, Chunyan; Qian, Dehui; Wang, Hang; Jiang, Hong; Deng, Mengyang; Huang, Lan (PloS one, 2012)
Cardiac stem cells (CSCs) can home to the infarcted area and regenerate myocardium. Stromal cell-derived factor-1[alpha]/C-X-C chemokine receptor type 4 (SDF-1[alpha]/CXCR4) axis is pivotal in inducing CSCs migration. However, the mechanisms remain unclear. This study set out to detect if SDF-1[alpha] promotes migration and engraftment of CSCs through the CXCR4/PI3K (phosphatidylinositol 3-kinase) pathway. In the in vitro experiment, c-kit+ cells were isolated from neonatal mouse heart fragment culture by magnetic cell sorting. Fluorescence-activated cell sorting results demonstrated that a few c-kit+ cells expressed CD45 (4.54%) and Sca-1 (2.58%), the hematopoietic stem cell marker. Conditioned culture could induce c-kit+ cells multipotent differentiation, which was confirmed by cardiac troponin I (cTn-I), [alpha]-smooth muscle actin ([alpha]-SMA), and von Willebrand factor (vWF) staining. In vitro chemotaxis assays were performed using Transwell cell chambers to detect CSCs migration. The results showed that the cardiomyocytes infected with rAAV1-SDF-1[alpha]-eGFP significantly increased SDF-1[alpha] concentration, 5-fold more in supernatant than that in the control group, and subsequently attracted more CSCs migration. This effect was diminished by administration of AMD3100 (10 [micro]g/ml, CXCR4 antagonist) or LY294002 (20 [micro]mol/L, PI3K inhibitor). In myocardial infarction mice, overexpression of SDF-1[alpha] in the infarcted area by rAAV1-SDF-1[alpha]-eGFP infection resulted in more CSCs retention to the infarcted myocardium, a higher percentage of proliferation, and reduced infarcted area which was attenuated by AMD3100 or ly294002 pretreatment. These results indicated that overexpression of SDF-1[alpha] enhanced CSCs migration in vitro and engraftment of transplanted CSCs and reduced infarcted size via CXCR4/PI3K pathway.